Perception of Knowledge Management Practices by Nigerian Fintech Founders - Olalekan, Olatunbosun; Adeleye, Deborah; Uyanwune, Chinaza (AFEBI Management and Business Review, 2024)
This study examines the perspectives of Nigerian fintech entrepreneurs on knowledge management (KM) techniques, with the goal of comprehending the influence of KM on innovation and decision-making. The study centers around 43 individuals who are founders or co-founders of fintech companies, all of whom are part of the Young Founders Community in Nigeria. Data was collected and analyzed using an online questionnaire distributed through Google Forms. The study involved descriptive and inferential statistics, along with theme analysis for qualitative replies. The findings indicate that the respondents typically consider their knowledge management systems to be effective. It was observed that frequent knowledge-sharing activities have a substantial impact on innovation and decision-making. The main obstacles mentioned encompass technological impediments, cultural opposition, and insufficient infrastructure. These observations emphasize the significance of strong knowledge management techniques in enhancing competitive advantage and emphasize the necessity for specific tactics to overcome difficulties in implementation. This study adds to the existing knowledge in the field of knowledge management (KM) by presenting factual data from a developing market setting. Additionally, it provides practical suggestions for improving KM systems in financial technology (fintech) companies. Subsequent investigations should delve into the enduring effects of knowledge management (KM) and conduct comparison analyses across many geographical areas and sectors.